Release Pattern of the Vascular Plasminogen Activator and Its Inbibitor in Human Postvenous Occlusion Plasma as Assessed by a Spectrophotometric Solid-Phase Fibrin-tPA Activity Assay - Anglés-Cano, E; Boutière, B; Arnoux, D; Masson, C; Contant, G; Benchimol, P; Sampol, J (Thrombosis and Haemostasis, 1987)
Vascular or tissue-type plasminogen activatbr(plasma t-PA) is the circulating physiological fibrinolytic enzyme of endothelial cell origin which function is regulated by fibrin and a specific inhibitor (PAI). To study the pattern of release of t-PA and the behavior of t-PA-PAI complexes in plasma. we determined t-PA activity in 44 healthy subjects before and after 10 min offorearm venous occlusion using a new spectrophotmnetrio solid-phase fibrin-tPA activity assay. The assay is based on 1) the high affinity binding of t-PA tofibrin, and 2) the detection of fibrin-bound t-PA by measuring the release of pNA from a chromogenic substrate in the presence of plasminogeu. Values at.rest were rather undetectable in plasma (0.05 ± 0.03 IU/ml, in 23 out of 44 samples) but were positively detected in all the euglobulins: 0.88 ± 0.68 IU/ml. After venous occlusion the majority ofplasmas (36 out of 44) shoWed a slight increase in t-PA activity (0.65 ± 0.63 IU/ml) as compared to the important level observed in all the euglobulins (9.78 ± 9.58 IU/ml). So, the ratio plasma/euglobulin t-PA activity was very low (0.06) and remained identical in both pre- and postocclusion samples. However, when diluted plasmas were tested the inhibitory effect disappeared and t-PA activity increased indicating that although t-PA circulates in a neutralized state it can be available for fibrinolysis. Since 1) no binding of α2 antiplasmin to fibrin in solid-phase could be demonstrated, 2) there was no correlation between α2 antiplasmin and t-PA activity, and 3) a PAI-depleted plasma with a normal content of α2 antiplasmin did not suppress the activity of t-PA, the inhibitory effect was attributed to PAL Our findings suggest that both t-PA and PAI are released. by venous occlusion and circulates in plasma as a t-PA-PAI complex.
Keywords: t-PA activity; PA inhibitor; Venous occlusion; Solid-phase fibrin; Spectrophotometric assay